Caracterização das ações antrópicas na microbacia hidrográfica do Rio dos Mangues, Porto Seguro-Bahia, Brasil - Bomfim, Antônio Ribeiro (2012)
The watershed of the River Wetlands is inserted in one of the most threatened of the world: the Atlantic forest. Due to its importance, mainly to meet part of the Porto Seguro - BA city, this study aimed to relate the influence of the socio-economic and environmental water in their behavior. The completion of the research will apply the following activities: use mapping and land use through pre-processing of satellite imagery, high resolution, and support software that work with Geographic Information System (GIS), and, characterization of the profile of farmers under the socioeconomic and environmental aspects. The work also seeks to show that saving the environment can be as interesting to the owner as agriculture and animal husbandry, especially for small farmers, promoting the generation of economic revenue to the conservation of natural resources on the property, as well as the environmental suitability the rural properties. The water with land use more intense suffered constant oscillation, confirming the importance of forest resources for biodiversity conservation and maintenance of the quantity and quality of water resources.